Race analysis and determination of stroke frequency - stroke length combinations during the 50-m freestyle event - Morais, J. E.; Barbosa, T. M.; Bragada, J. A.; Nevill, A. M.; Marinho, D. A. (Journal of Sports Science & Medicine, 2023)
The aims of this study were to: (1) analyze and compare the stroke kinematics between junior and senior elite male swimmers in every section of the race during the 50-m freestyle event, and; (2) identify stroke frequency (SF)-stroke length (SL) combinations on swim speed independently for junior and senior swimmers in each section of the 50-m freestyle event. Eighty-six junior swimmers (2019) and 95 seniors (2021) competing in the 50-m long course meter LEN Championships were analyzed. The t-test independent samples (p = 0.05) were used to compare juniors and seniors. The SF and SL combinations on swim speed were explored using three-way ANOVAs. Senior swimmers were significantly faster in the 50-m race than juniors (p < 0.001). Speed presented the largest significant difference (p < 0.001) in section S0-15 m (start until the 15th meter mark) being seniors fastest. Both junior and senior swimmers revealed a significant categorization (p < 0.001) by stroke length and stroke frequency in each race section. It was possible to model several SF-SL combinations for seniors and juniors in each section. The fastest swim speed in each section, for seniors and juniors independently, was achieved by a SF-SL combination that may not be the fastest SF or the longest SL. Coaches and swimmers must be aware that despite the 50-m event being an all-out bout, several SF-SL combinations were observed (independently for juniors and seniors), and they differ between race sections.